Proposta de enlace indutivo para alimentação de dispositivos implantáveis - Braga, Eduardo Felipe Ardigo (2020)
The use of implantable medical devices wirelessly powered has gained prominence with the application of inductive couplings for this purpose. This technique allows for great efficiencies in the relation between transmitted power and delivered to the implant. The devices can be for the most varied purposes, and in the present work, it was defined the development of an inductive coupling to power biomedical devices in general. Therefore, to achieve the objective, it is necessary to present some concepts and carry out experiments in order to compare the results. The first comparison is for the set with 2, 3, or 4 coils, it is important to analyze which one best fits the desired application. The experiments were also carried out with different loads, 10, 22, 47, and 100 Ω, to observe the behavior of the system due to the variation of the load to be fed. With the aid of the analysis of theoretical concepts, it was possible to elaborate a comparison between theoretical data, calculated through the equations found and simulations performed, and practical data, obtained through the experiments carried out. Commercial coils were then used in order to carry out the experiments. Some of the coils used in the experiments had a ferrite attached to them, other coils had the ferrite removed. Thus, it was important to carry out an experimental study about the interference of ferrite in the coupling between the coils and, consequently, in the efficiency of the sets. This issue of ferrite interference is something that has not been found in the literature, só it presents a new and essential research field for future applications like the one presented in this work. Thus, the interference of ferrite in the inductance and in the magnetic coupling coefficient between them was observed. The results of the experiments and comparisons made allow the definition of the best parameters for the construction of the desired set, in order to meet the biomedical devices powered via wireless energy transfer by inductive coupling. The analyzed distances varied from 0 to 10 mm and it was possible to observe that in the shortest distances in this range, the 2-coil system has better efficiencies over the others. However, in the relationship between distance and efficiency, the 3-coil system was the one with the best results, since, with the help of the repeater coil, the system is able to offer greater efficiencies over greater distances, between 8 and 10 mm. The 4-coil system had lower efficiencies, which is due to losses in the intermediate circuits since this system has many couplings between non-adjacent coils, which may hinder its efficiency.